Testing the Salience of Phenotypic Bias as Basis of Evaluation of Attractiveness among University Students - Quintos, Mark Anthony; Iwayama, Minami (Social Sciences and Development Review, 2020)
This research aimed to look into the influence of skin complexion on the attractiveness of people. The objectives of the study are the following: determine if a change in the skin color causes a significant difference in the perceived attractiveness of models, identify if the skin color of models are a salient basis for their perceived attractiveness, and distinguish if a subject’s actual skin color, skin color preferences for self, and for one’s ideal partner have a significant relationship with one’s perception of the models’ attractiveness. Data were obtained through an experiment which required the subjects to rate the attractiveness of 13 models with varying skin tones. Results were analyzed using descriptive statistics, test of population on paired samples, and spearman rank correlation. The results of the study indicate that phenotypic bias is prevalent among the subjects. The results showed a significant difference in the scores of the models which are always in favor of the models with lighter skin. The results also indicated that skin color is part of the factors considered by majority of the subjects in evaluating of the attractiveness of the models. Results further indicated that the subjects have a preference for lighter skin both for themselves and their ideal partner, and that this preference is salient in their evaluation of attractiveness. This relationship between phenotypic bias and evaluation of attractiveness as mediated by socio-demographic characteristics such as age, sex, and relationship status were also explored in the study.